An Open-Path Optical Fibre Sensor For Ammonia Measurement In The Ultra Violet Region - Hadi, Manap; Nor Mazlee, Norazmi; K., Suzalina; M. S., Najib (Asian Research Publishing Network, 2016)
This paper describes an optical fibre sensor system for displaying of ammonia gas spectrum. An open path optical technique is used to analyze the absorption lines of ammonia within the Ultra Violet Region. Experimental results describing the operation of the sensor with varying gas concentrations are presented and are compared with recorded results calculated from measured experimental flow rates. The results show the sensor is capable of detecting small concentration changes of ammonia